Designing of a Quality Audit Methodology for IT Support Service : Development of a quality audit criteria - Attie, Romain (My University, 2021)
In today's business landscape, IT Support has become a key service due to the increasing prominence of information technology in companies. In addition, many companies decide to outsource their IT services, partly to ensure its quality. However, despite the implementation of contracts and Service Level Agreements between the parties, which formalise all the conditions for the successful delivery of this service, IT service quality is nevertheless not guaranteed. This thesis therefore focuses on monitoring the quality of a Service Desk through an audit methodology in order to increase its quality. Indeed, this thesis is a Design Science research based on a case study conducted within a company with the aim of developing a solution, based on an audit methodology, to measure the weak points of its IT support service in order to later elaborate an action plan to improve its quality. To this end, quantitative surveys among users and service providers were conducted in order to develop an audit criteria norm for the company under study. This research produced a number of key findings. Firstly, it was found that the main factors influencing service quality are behaviour of service providers, competence of service providers and the surrounding environment such as different management and communication tools. It was also determined that for this case study, a lack of quality results in a lack of communication between users and providers, long waiting times, as well as undelivered service. Furthermore, the audit methodology for the research was inspired by the ITIL best practice, and more specifically its section on Continuous Service Improvement. The final solution is represented in the form of an analysis grid with several checkpoints. In the case, these checkpoints are selected through the analysis of the questionnaires, representing the potential weak points of the support service to be monitored. These checkpoints are measured through indicators, and if they are confirmed to be below the threshold, recommendations for remedial action are proposed. Finally, this analysis grid was validated by the involved company and accepted for a test implementation. The aim is that this audit report will be reproduced on a regular basis and that the analysis grid will evolve as the IT Support Service improves.
Keywords: IT Service Support, Quality Audit Methodology, ITIL, Service Desk, Monitoring, Audit Criteria